Benthic ecology of semi-natural coastal lagoons, in the Ria Formosa (Southern Portugal), Exposed to different water renewal regimes - Gamito, Sofia (2013)
Several studies in semi-natural coastal lagoons in the Ria Formosa lagoonal system have been carried out. These man-made water reservoirs behave as small lagoons with one opening to the tidal channels, which may be intermittent. Because of their size, these reservoirs are ideal sites for ecological studies. Water quality and macrobenthic fauna were analysed in five water reservoirs. All reservoirs received the same incoming water through a tidal channel, but they differed in water renewal regime. Multidimensional Scaling (MDS) and Discriminant Analysis were used to evaluate the similarity among sites, stations and sampling occasions. Different levels of taxonomic resolution (family, large taxonomic groups and phylum level) were also evaluated. The separation of sites and stations became unclear using high taxonomic levels. Results from the multivariate analyses suggest a slight differentiation of the stations according to sampling occasion but a clear differentiation of the several water reservoirs. Some of the lagoons studied with low water renewal rates showed strong environmental variations. They were characterised by low diversity indexes and abundance of small-sized organisms. Other lagoons, with high water renewal rates, showed low environmental variation and well diversified and structured benthic communities. The main environmental factor that seems to affect the benthic communities was the variation in salinity between neap and spring tides, which is related with the water renewal regime. Coastal lagoons offer a protected shallow habitat, which can be highly productive. Well structured communities, controlled by k-strategists, can develop and settle in leaky lagoons, that is, lagoons with wide entrance channels and tidal currents which guarantee a good water renewal. In these lagoons, biomass can accumulate in large organisms. In contrast, lagoons with a single narrow entrance, that may be closed for long periods, are characterised by persistent physical stress and are dominated by communities of small-sized r-strategists.